A Thermoelectrically Cooled nBn Type‐II Superlattices InAs/InAsSb/B‐AlAsSb Mid‐Wave Infrared Detector. Issue 6 (14th February 2020) - Martyniuk, Piotr; Michalczewski, Krystian; Tsai, Tsung-Yin; Wu, Chao-Hsin; Wu, Yuh-Renn
Abstract : Herein, an nBn barrier mid‐wave infrared InAs/InAsSb ( x Sb  = 0.4) type‐II superlattice (T2SL) detector operating in the thermoelectrical (TE) cooling condition is reported. AlAsSb (Sb‐composition, x Sb  ≥ 0.975) is shown not to introduce an additional barrier in the valence band in the analyzed temperature range (≥200 K) reached by four‐stage TE cooling in nBn barrier architectures with a T2SL InAs/InAsSb active layer. The dark current and photocurrent produced are analyzed in relation to the barrier and contact layer doping, with the Sb composition of the barrier indicating the optimal architecture. The results of the simulation are compared with the experimental results of the HgCdTe and InAsSb nBn barrier detectors. A detectivity of ≈10 10  cmHz 1/2  W −1 at 200 K is reported without an immersion lens (≈10 11  cmHz 1/2  W −1 is reported for an immersed detector). Abstract : Herein, an nBn mid‐wave infrared InAs/InAsSb type‐II superlattice detector is reported. AlAsSb is shown not to introduce an additional barrier in the valence band. The dark current and photocurrent are analyzed indicating the optimal architecture. The results are compared with the HgCdTe and InAsSb nBn detectors.